The Students’ Writing Ability in Descriptive Text of the Senior High School Students in Berau - Annisa Raudatus Sa’adah (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2020)
English in Indonesia is a foreign language that should be learned and mastered by students. Education is a process of fundamental skills intellectual and emotional. The aim of education is to improve the quality of students in Indonesia, especially in writing. There are so many ways conducted by educational institution in improving students English quality in Indonesia. One of the institutions is SMA Negeri 1 Berau. Based on research conducted the researcher found that in SMAN Negeri 1 Berau has a language major program. The objective of this research is to know the students’ writing ability in descriptive text and their problems in writing of tenth grade language major students. This research used descriptive quantitative. The instruments are writing assessment and interview. The technique of collecting data, the researcher asked students to write a descriptive text with a place as a topic to measure the students writing ability and asked the students several questions to know their problem in writing. The data analysis technique was scoring based on writing rubric. The assessing of writing focused on five components, they are content, organization, vocabulary, language use, and mechanic. The assessing of writing had been given to some of the students of tenth grade language major students in SMA Negeri 1 Berau that consist of 8 students. Based on the data finding, it showed that writing ability of tenth grade language major students in SMA Negeri 1 Berau was 3,75 that categorized into mediocre level. The average category of content was mediocre, the average category of the organization was mediocre, the average category of vocabulary was good, the average category of the language used was mediocre, and the average category of the mechanic was mediocre. From the interview, the students have difficulties in finding references in writing, word choices, arranged words to be a good sentence, arranged sentences to be a good paragraph, and developing the idea. Most of them admit difficlties with the language use. Some of them said they have no probems with vocabulary and mechanic such as capitalization, punctuation, and spelling.